Acute Myocardial Infarction and Massive Pulmonary Embolus Presenting as Cardiac Arrest: Initial Rhythm as a Diagnostic Clue. (14th July 2013) - Bhatia, Nirmanmoh; Vongooru, Haree; Ikram, Sohail
Abstract : Myocardial infarction (MI) and massive pulmonary embolism (MPE) are common causes of cardiac arrest. We present two cases with similar clinical presentation and EKG findings but different initial rhythms. Case  1 . A 55-year-old African American male (AAM) was brought to the emergency room (ER) with cardiac arrest and pulseless electrical activity (PEA). Twelve-lead electrocardiogram (EKG) was suggestive of ST segment elevations (STEs) in anterolateral leads. Coronary angiogram did not reveal any significant obstruction. An echocardiogram was suggestive of a pulmonary embolus (PE). Autopsy revealed a saddle PE. Case  2 . A 45-year-old AAM with a history of coronary artery disease was brought to the ER after ventricular fibrillation (VF) arrest. Twelve-lead EKG was suggestive of STE in anterior leads. Coronary angiogram revealed in-stent thrombosis. In cardiac arrests, distinguishing the two major etiologies (MI and MPE) can be challenging. PEA is more commonly associated with MPE versus MI due to near complete obstruction of pulmonary blood flow with an intact electrical conduction system. MI is more commonly associated with VF as the electrical conduction system is affected more often by ischemia. In conclusion, the previous cases illustrate that initial rhythm may be a vital diagnostic clue.